Kompetencje nauczycieli w zakresie edukacji muzycznej uczących w klasach I-III w szkole ogólnodostępnej = The skills of teachers in the field of music education students in classes I-III in mainstream school - Matuszak, Lucyna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The content of the article presents the classification of the competence of teachers. It shows how nowadays it is impossible for one person - a teacher teaching in classes I-III of primary school - to have a high level competence in all education, especially in the field of music education.
Keywords: kompetencje nauczyciela; sylwetka współczesnego nauczyciela; edukacja muzyczna; competence of the teacher; silhouette of the contemporary teacher; musical education